2023
DOI: 10.1093/braincomms/fcad095
|View full text |Cite
|
Sign up to set email alerts
|

The presence, nature and network characteristics of behavioural phenotypes in temporal lobe epilepsy

Abstract: The relationship between temporal lobe epilepsy and psychopathology has had a long and contentious history with diverse views regarding the presence, nature, and severity of emotional-behavioral problems in this patient population. To address these controversies, we take a new person-centered approach through the application of unsupervised machine learning techniques to identify underlying latent groups, or behavioral phenotypes. Addressed are the distinct psychopathological profiles, their linked frequency, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In short, a key point in our data is that highly individualized networks were abnormal in TLE patients before they showed significant cognitive impairment. This spectrum perspective on the key cognitive phenotypes(Bell et al, 2011; Hermann et al, 2021; Struck et al, 2023) likely has implications for other disorders of cognitive impairment, perhaps even for normal aging. That is, highly individual, personal brain networks arising from an individual’s unique experiences and learning may possess an earlier vulnerability to brain disease compared to canonical brain networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In short, a key point in our data is that highly individualized networks were abnormal in TLE patients before they showed significant cognitive impairment. This spectrum perspective on the key cognitive phenotypes(Bell et al, 2011; Hermann et al, 2021; Struck et al, 2023) likely has implications for other disorders of cognitive impairment, perhaps even for normal aging. That is, highly individual, personal brain networks arising from an individual’s unique experiences and learning may possess an earlier vulnerability to brain disease compared to canonical brain networks.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that cognitive status in TLE can be characterized by several cognitive phenotypes, involving one or more groups with expected cognitive anomalies, but also a group with an unexpected, intact cognitive profile. (Elverman et al, 2019; Hermann et al, 2020; Hermann et al, 2021; Reyes et al, 2019; Struck et al, 2023) In this context, a direct comparison of intrinsic brain systems in TLE patients with distinct neurocognitive profiles could have significant implications. We argue that investigating TLE patients with “intact” versus “impaired” neurocognitive profiles, interrogating for the presence of macroscopic intrinsic connectivity networks (normative and highly individual), characterizing the organizational properties of each, and, lastly, testing for a spectrum shift in these networks when transitioning from “intact-to-impaired” cognitive status,(Tracy et al, 2021) will help us understand how cognitively “intact” TLE patients support their cognitive functioning while other TLE patients display lost functionality.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the influence of coexistent mental disorders must be considered, including anxiety, depression, and apathy. Several studies have focused on the impairment of several cognitive domains and have detected distinct groups with unique clinical and cognitive phenotypes and neuroimaging profiles in patients with focal epilepsy 71–73 . Following the DSM‐5 system and the IC‐CoDE approach, TLE with HS could also be divided into different groups, such as intact cognitive phenotype, subjective cognitive decline, and memory‐impaired with and without impairment of other domains.…”
Section: Discussionmentioning
confidence: 99%